2000
DOI: 10.1046/j.1442-200x.2000.01312.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of interferon‐α2b treatment in children with chronic hepatitis B who have previously undergone therapy for cancer

Abstract: In conclusion, a 12 month course of IFN-alpha2b induces some beneficial effects on virologic, biochemical and histologic indices in children with chronic hepatitis B who have previously undergone therapy for cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In a study from Turkey, 11.6% of children surviving malignancy had positive hepatitis B surface antigen (HBsAg) (1). Interferon (IFN) alone (6 or 12 months) or prednisone with IFN‐α and famciclovir were used for treatment of chronic hepatitis B (CHB) infection and response to treatment was observed in approximately 25% of these children (2–4). Kocak et al (2) reported that complete response, defined as clearance of both HBV DNA and hepatitis B e antigen (HBeAg) and seroconversion to anti‐HBe was observed in two (25%) out of eight patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study from Turkey, 11.6% of children surviving malignancy had positive hepatitis B surface antigen (HBsAg) (1). Interferon (IFN) alone (6 or 12 months) or prednisone with IFN‐α and famciclovir were used for treatment of chronic hepatitis B (CHB) infection and response to treatment was observed in approximately 25% of these children (2–4). Kocak et al (2) reported that complete response, defined as clearance of both HBV DNA and hepatitis B e antigen (HBeAg) and seroconversion to anti‐HBe was observed in two (25%) out of eight patients.…”
mentioning
confidence: 99%
“…Kocak et al (2) reported that complete response, defined as clearance of both HBV DNA and hepatitis B e antigen (HBeAg) and seroconversion to anti‐HBe was observed in two (25%) out of eight patients. Kasirga et al (3) reported that three (27.3%) out of 11 patients had seroconversion to anti‐HBe. Long‐term results of treatment were not reported in these studies.…”
mentioning
confidence: 99%